UNRAVELING STUDENT INSIGHTS: QUIZIZZ IN ENGLISH LEARNING AT A VOCATIONAL HIGH SCHOOL IN CIREBON - Herawati, Nurul; Erawati, Turini (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2023)
Along with the times, the use of technology in learning becomes dominant. One alternative online learning tool that can be utilized is Quizizz. This research examined how students view the incorporation of Quizizz for English learning. Student perceptions were utilized as a metric to gauge the effectiveness of the teaching and learning process, as well as to assess the methodologies employed by educators. The success of teaching and the learning process is significantly influenced by students' perceptions. By understanding these perceptions, educators can better grasp students' learning requirements and tailor their teaching approach accordingly. Consequently, the students perceptions can influence their motivation in learning English. Thus the interactive online media was chosen in order to increase their enagagment throughout the learning journey. Furthermore, the qualitative case study was designed for this study by spreading questionnaires and conducting interviews to collect the data. The Likert Scale was employed for data analysis. The subjects involved were 11th-grade students from a vocational high school. The results of this study revealed that students have a positive perception towards the utilization of Quizizz. Quizizz was a fun and interesting web-based online learning that was easy to use and encouraged students’ motivation toward the leaderboard and display. Hence, utilizing Quizizz positively influenced students' perspectives. Quizizz serves as a viable web-based alternative for online learning and facilitating the acquisition of essential 21st-century skills.